Pengembangan Lembar Kerja Pembelajaran IPA Berbasis Al Quran untuk siswa MI - Pipih Nurhayati (Al Ibtida: Jurnal Pendidikan Guru MI, 2017)
AbstractThis study aims to provide a reference to  developing science worksheet based on Quran. This study using the Research and Development (RnD) method with limited implementation. Subject of this study were 33 students SD / MI in Cimahi who determined purposively. The research data came from observations, expert judgment, questionnaires and interviews. Plant is science theme which used which is divided into several sub-themes: the classification of plants, growth and reproduction of plants. Worksheets learning assessed from several aspects,the effectiveness of lab work, pedagogy, content, technical, and aesthetic. The results obtained show that the worksheet has the practical effectiveness value was excellent (93.3%). Strong technical aspects (81.25%), as well as aspects of pedagogy, content and aesthetic is very strong (87.5%). After following the learning, students gave positive responses (93%) of the science worksheet based Quran.Keywords: worksheet, based Quran, MI